Smart Mobile In-Vehicle Systems Next Generation Advancements - Schmidt, Gerhard; Abut, Huseyin; Takeda, Kazuya; Hansen, John H.L (Springer New York : Imprint: Springer, 2014)
This is an edited collection by world-class experts, from diverse fields, focusing on integrating smart in-vehicle systems with human factors to enhance safety in automobiles. The book presents developments on road safety, in-vehicle technologies and state-of-the art systems. Includes coverage of DSP technologies in adaptive automobiles, algorithms and evaluation of in-car communication systems, driver-status monitoring and stress detection, in-vehicle dialogue systems and human-machine interfaces, challenges in video and audio processing for in-vehicle products, multi-sensor fusion for driver identification and vehicle to infrastructure wireless technologies.